EVALUATION OF ENRICHMENT BILINGUAL PROGRAMS (Case Study in SMP Negeri 3 Kota Tangerang Selatan) - hasyim hasyim (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to assess the gap in Enrichment Program in SMPN 3 Tangerang Selatan. This research used DEM (Discrepancy Evaluation Model) model or gap evaluation model which consists of input, process and output aspects. This research used qualitative approach with descriptive method through technique of data analysis in the form of interview, observation and document study. Sources of data were obtained from the school principal, program coordinator, vice principal of facilities and infrastructure, treasurer of the program, administration, classroom teachers and enrichment learner. Evaluation results show that there is a gap in enrichment program at SMPN 3 Tangerang Selatan. In the mean input aspect the gap is 30.08% is in the low category. In the mean process aspect the gap is 35.02% is in the medium category. In the output aspect, the average gap of 7.19% is in the low category.